Deubiquitination of FANCD2 is required for DNA crosslink repair - Oestergaard, Vibe H; Langevin, Frederic; Kuiken, Hendrik J; Pace, Paul; Niedzwiedz, Wojciech; Simpson, Laura J; Ohzeki, Mioko; Takata, Minoru; Sale, Julian E; Patel, Ketan J (Molecular cell, 2007)
Monoubiquitination of FANCD2 and PCNA promotes DNA repair. It causes chromatin accumulation of FANCD2 and facilitates PCNA's recruitment of translesion polymerases to stalled replication. USP1, a protease that removes monoubiquitin from FANCD2 and PCNA, was thought to reverse the DNA damage response of these substrates. We disrupted USP1 in chicken cells to dissect its role in a stable genetic system. USP1 ablation increases FANCD2 and PCNA monoubiquitination but unexpectedly results in DNA crosslinker sensitivity. This defective DNA repair is associated with constitutively chromatin-bound, monoubiquitinated FANCD2. In contrast, persistent PCNA monoubiquitination has negligible impact on DNA repair or mutagenesis. USP1 was previously shown to autocleave after DNA damage. In DT40, USP1 autocleavage is not stimulated by DNA damage, and expressing a noncleavable mutant in the USP1 knockout strain partially rescues crosslinker sensitivity. We conclude that efficient DNA crosslink repair requires FANCD2 deubiquitination, whereas FANCD2 monoubiquitination is not dependent on USP1 autocleavage.